Ganoderma weixiensis (Polyporaceae, Basidiomycota), a new member of the G. lucidum complex from Yunnan Province, China - Ye, Lei; Karunarathna, Samantha C.; Mortimer, Peter E.; Li, Huili; Qiu, Ming-Hua; Peng, Xing-Rong; Luangharn, Thatsanee; Li, Yun-Ju; Promputtha, Itthayakorn; Hyde, Kevin D.; Xu, Jian-Chu (Phytotaxa, 2019)
Despite the ecological and economic significance of Ganoderma, the taxonomy of this group of mushrooms remains largely unresolved. In line with an attempt to further our understanding of Ganoderma, we describe a new species collected from Yunnan Province, China. Ganoderma weixiensis is described here based on the morphological characteristics and phylogenetic analyses of combined ITS, LSU and TEF1-α gene regions. This new species is characterized by a reddish-brown pileus, cream colored pore surface and context, eccentrically or centrally attached stipe, and broadly ellipsoid basidiospores Comparisons of the morphological characteristics of G. weixiensis and its close relatives G. lucidum and G. leucocontextum are also presented.